Effect of pasture management on enteric methane emissions from goats - Meister, Naomi Cristina [UNESP]; Cardoso, Abmael da Silva [UNESP]; Alari, Fernando Oliveira; Lemos, Nailson Lima Santos; Frighetto, Rosa Toyoko Shiraishi; Malheiros, Euclides Braga [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Springer Nature, 2021)
The effect of pasture management on CH4 emissions was investigated from goats in a tropical climate. Two experiments were conducted in a “Tanzania Guinea grass” (Panicum maximum Jacq.) pasture to assess enteric CH4 production in a completely randomized design. Emissions from light, moderate, and heavy grazing intensities were analyzed in the first experiment, and variations between grazing days were explored in the second experiment. Grazing intensity was defined as 2.4, 1.6, and 0.8 post-grazing leaf area index. Pasture management employed intermittent grazing with variable stocking rate using Anglo Nubian female adult goats. SF6 tracer gas technique was used to measure CH4 production. Grazing intensity was not found to affect CH4 emissions per animal, dry matter forage intake (DMI), and gross energy (GE) intake. However, the second experiment showed that CH4 production was influenced by the grazing day. CH4 emissions were 18.1 g day−1, and the variables were 0.88 g kg−1 of metabolic weight, 17.45 g kg−1 of DMI, and 5.5% of GE. CH4 production increased linearly with the grazing day, possibly reflecting a reduction in forage quality. These findings suggest that the day of occupation in intermittent grazing has a greater effect on CH4 emissions than that by grazing intensity and that a single day grazing of Tanzania Guinea grass could mitigate CH4 emissions.
Keywords: CH4 mitigation; Pasture management strategy; Ruminants; Tanzania Guinea grass